Human resource management practices and organizational commitment in the Sarawak education department, Kuching - Norestherwati, Abdullah (2001)
The purpose of this study is to determine the perception of Sarawak Education Department staff toward organizational commitment and the human resource management practices that influence it. Specially, the objective of the study is to determine if there is any difference among staff with varied demographic characteristics such as gender, age, race, academic qualifications and years of service in term of their perception toward organizational commitment. other objectives are to determine whether there is any significant relationship between organizational commitment and certain human resource management practices practiced in the workplace and the most dominant human resource management practice that influence organizational commitment of employees.The findings of the study showed that the majority (92%) of the staff survayed in the department have a positive perception toward organizational commitment.